Performance investigation of a solar powered thermoelectric refrigerator - Saidur, Rahman; Masjuki, Haji Hassan; Hasanuzzaman, M.; Mahlia, T.M.I.; Tan, C.Y.; Ooi, J.K.; Yoon, P.H. (International Journal of Mechanical and Materials Engineering, 2008)
This paper describes the development stages and performance of a solar powered thermoelectric refrigerator. It is carried out by installing a conventional thermoelectric refrigerator in a stand alone photovoltaic system for household usage. This photovoltaic driven refrigerator is powered by a field of solar panels, a battery bank, a solar charge controller, and an inverter. In this project, the output power of the photovoltaic system and the capability of the battery bank are determined. A compact thermoelectric refrigerator of 22 watts is applied to be investigated in respect to cooling effect produced. To make the device portable, daytime use and nighttime use of the refrigerator are treated in different ways. The effect of door-opening upon the cooling temperature produced by the photovoltaic driven thermoelectric refrigerator is investigated too. In order to efficiently operate this solar powered refrigerator, the sizing of this stand-alone photovoltaic system and the optimum tilt angle of the photovoltaic array must firstly be determined to maximize the electricity generation for matching the load requirement.